Belajar Sejarah Indonesia: Aplikasi Media Pembelajaran Sejarah untuk Siswa Kelas X SMK - Dimas Eko Pujianto, Dimas Eko Pujianto; Sugiyanto, Sigit (Utility Project Solution, 2023)
Around 58% of smartphone users are teenagers aged 14-17 or middle school to high school or vocational school students. With a fairly large presentation, the motive for owning this cellphone is of concern because its use is often in a negative direction that has nothing to do with learning activities. With this problem, the author took the initiative to create Android-based learning media which was created using Canva and Construct 3 to attract the interest of vocational school students, especially in studying History. This learning media creation model uses the ADDIE model with the help of media experts and material experts to assess learning media called Learning Indonesian History (BSI). After being implemented in class for vocational high school students in grade tenth, they agree that Learning Indonesian History (BSI) succeeded in attracting students’ interest in learning History by presenting materials’ review and relevant exercises.